If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 200 + 6m = 600 + -6m Solving 200 + 6m = 600 + -6m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '6m' to each side of the equation. 200 + 6m + 6m = 600 + -6m + 6m Combine like terms: 6m + 6m = 12m 200 + 12m = 600 + -6m + 6m Combine like terms: -6m + 6m = 0 200 + 12m = 600 + 0 200 + 12m = 600 Add '-200' to each side of the equation. 200 + -200 + 12m = 600 + -200 Combine like terms: 200 + -200 = 0 0 + 12m = 600 + -200 12m = 600 + -200 Combine like terms: 600 + -200 = 400 12m = 400 Divide each side by '12'. m = 33.33333333 Simplifying m = 33.33333333
| (3/(3x-1))-(5/(3x-1))=0 | | 2x-5.5=-x/5*1/2x | | 3/(2X+1)=X+1 | | (8-y)(3+4)=0 | | 3x+-0.3(6-x)=3.9 | | 4(X+3)+260/X | | 9x-2(x-6)=7x+2 | | 10+.99d=.89d | | (9/(x-2))(7/(x-5))=0 | | 10+.99d=.88d | | 2y-5=x-10 | | ((x+3)/(x-1))/((x^2+x)/(x-1)) | | 653+456= | | 653+456=1209 | | 0.8x+6.37=0.4x+9.57 | | 4(w+3)=3-15 | | 2(3.5n+6)=2.5n+(-2) | | 3xa=2b | | 0.30(12)+0.5x=0.15(18+x) | | E^2x-2=14 | | 3ax=3b | | (10y^2+27Y-15)/(2Y+7) | | 8c=9c+3 | | 5X+39+9X-125=180 | | 38(7-2.5x)=14(2x-10)+61.6 | | 7x-3=x/6+5 | | 6X+27+7X-9=96 | | 2(8y-4.4)+7=6(7y-0.3) | | (y+7)/(y^2-8y+7)=(1/(y-1))-(1/(y-7)) | | (x^2-16)/(x^2-3x-4)=0 | | (0.25+0.083+0.3)x0.3/0.5 | | 11(x-2)-4=9x+4 |